Comparison of Seroma Formation with Harmonic Scalpel Versus Monopolar Electrocautery in Axillary Dissection following Modified Radical Mastectomy - Zahid, Abrar; Javed, Tehreem; Kaleem, Muhammad; Andrabi, Wajeeha Imran; Jamil, Talha; Qureshi, Sidra Shoaib; Rabbani, Shaukat; Andrabi, Syed Imran Hussain; Butt, Hasnat Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer is cancer that forms in the cells of the breasts. Despite of the emergence of the breast conservation technique modified Radical Mastectomy still remains the most commonly performed surgery for CA Breast. The Harmonic scalpel is a surgical instrument used to simultaneously cut and cauterize tissue. Aim: To compare the frequency of seroma formation with harmonic scalpel versus monopolar electrocautery in axillary dissection following modified radical mastectomy. Methods: This randomized control trial was conducted in the Department of General Surgery, Lahore General Hospital and Ghurki Trust Teaching Hospital, Lahore. 60 patients were enrolled. Two groups were made by applying lottery method. One group is treated with hormonic scalpel and other with electrocautery. All surgeries were done under general anesthesia by two surgical teams. After surgery, patients shifted in post-surgical wards and will be followed- up there for 7 days. Seroma formation was noted. All the collected data was entered and analyzed on SPSS version 21. Results: The mean age in harmonic scalpel group was 49.87± 8.67 years and in electrocautery group was 49.87± 8.67 years. The seroma formation in harmonic scalpel group was noted in 5(16.7%) patients whereas the seroma formation in electro cautery group was found in 11(36.7%) patients (p-value=0.080). Conclusion: This study concluded that the harmonic scalpel group showed lower rate of seroma formation than to electrocautery group, however statistically both groups are equally effective